2023
DOI: 10.1002/jmv.29152
|View full text |Cite
|
Sign up to set email alerts
|

Its all about IFN‐λ4: Protective role of IFNL4 polymorphism against COVID‐19‐related pneumonia in females

Sanja Matic,
Dragan Milovanovic,
Zeljko Mijailovic
et al.

Abstract: Despite the pivotal role of IFN‐λs in the innate immune response, the data on its genetic polymorphism in relation to COVID‐19 severity are scarce and contradictory. In the present study, we aimed to determine if the presence of the most frequent functional single nucleotide polymorphisms (SNPs) of the two most important IFN‐λs coding genes, namely IFNL3 and IFNL4, alters the likelihood of SARS‐CoV‐2‐infected patients to develop more severe form of the disease. This observational cohort study involved 178 COVI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Also, the authors observed that the likelihood of pneumonia development remained significantly associated with IFNL4 polymorphism, especially in females. These results suggest that IFNL4 rs12979860 and rs368234815 polymorphisms could predict the risk of COVID-19-related pneumonia development in females ( 23 ).…”
Section: Ifns In Sars-cov-2 Infectionmentioning
confidence: 76%
“…Also, the authors observed that the likelihood of pneumonia development remained significantly associated with IFNL4 polymorphism, especially in females. These results suggest that IFNL4 rs12979860 and rs368234815 polymorphisms could predict the risk of COVID-19-related pneumonia development in females ( 23 ).…”
Section: Ifns In Sars-cov-2 Infectionmentioning
confidence: 76%